Цифровізація військового обліку в Україні: правові проблеми та шляхи їх вирішення - Панова, І. В.; Panova, I. V.; Панова Ірина Вікторівна (Вісник Харківського національного університету внутрішніх справ. – 2024. – № 1 (104), ч. 1. - С. 251-260, 2024)
Досліджено проблемні питання організаційного та правового забезпечення цифровізації (дигіталізації) військового обліку призовників, військовозобов’язаних і резервістів, який ведеться органами військового управління. Запропоновано поширити концепцію роботи державних органів «Держава у смартфоні» на імперативну діяльність суб’єктів владних повноважень у сфері військового обліку. Наголошено на пріоритетності в окремих випадках відомостей цифрового військового обліку над інформацією, наявною в розпорядженні органів військового управління. Науково обґрунтовано зміни та доповнення до чинного законодавства з питань ведення Єдиного державного реєстру призовників, військовозобов’язаних та резервістів.

The article is devoted to a scientific study of the practice of maintaining military records of conscripts, persons liable for military service and reservists in Ukraine and identifying the main practical problems of processing conscripts’ data in electronic form, including under martial law. The main goal of the article is to establish certain problems of maintaining the Unified State Register of conscripts, persons liable for military service and reservists and ways to solve them. The methodology of the research is based on the method of system analysis, comparative and special legal methods. Based on the research, the author improves the scientific views on the legal understanding of the introduction of digitalisation of military registration as a form of fulfilment by Ukrainian citizens their constitutional duty to protect the Motherland and military service. The legal shortcomings of organising and maintaining military records in digital form are pointed out, and the ways of solving the identified problems are proposed. The following conclusions have been drawn from the study. The need to implement the concept of the “State in a smartphone” has been pointed out not only to serve citizens in terms of providing them with services or reporting violations committed by them. The whole range of actions related to state records and registers, including military ones, should be implemented using modern means of state work with citizens. It has been proposed to establish the priority of information entered in the Unified State Register of Conscripts, Persons Liable for Military Service and Reservists over information held by the bodies that maintain the register, provided that such information is entered later or received automatically from other state registers. The need to amend the laws of Ukraine “On Military Duty and Military Service” and “On the Unified State Register of Persons Liable for Military Service, Conscripts and Reservists” has been scientifically substantiated. The need to develop a software and hardware complex for the functioning of the “Electronic Office of the Defender” and legal regulation of its work has been emphasized. The obtained results of the study can be used in the development of changes in the legislation of Ukraine and the improvement of law enforcement practices in the field of military accounting in Ukraine.

Исследованы проблемные вопросы организационного и правового обеспечения цифровизации (дигитализации) военного учета призывников, военнообязанных и резервистов, проводимого органами военного управления. Предложено распространить концепцию работы государственных органов «Государство в смартфоне» на императивную деятельность субъектов властных полномочий в сфере военного учета. Отмечена приоритетность в отдельных случаях сведений цифрового военного учета над информацией, имеющейся в распоряжении органов военного управления. Научно обоснованы изменения и дополнения в действующее законодательство по вопросам ведения Единого государственного реестра призывников, военнообязанных и резервистов.
Digitization of military records in Ukraine: legal problems and ways to solve them
Keywords: цифровізація; дигіталізація; військовий облік; державний реєстр; правове регулювання; digitalisation; military registration; state register; legal regulation; цифровизация, дигитализация, военный учет, государственный реестр, правовое регулирование; дигитализация; военный учет; государственный реестр; правовое регулирование